Effect of Helicobacter pylori eradication on remnant stomach neoplasms after curative gastrectomy (HELP-GC): Protocol of a HELP-GC randomized controlled trial. - Chang Seok Ko; Jin Hee Noh; Young Soo Park; Jeong Hwan Yook; Hwoon-Yong Jung; In-Seob Lee; Ji Yong Ahn; Ji Sung Lee (PLoS ONE, 2025)
Background Limited research has examined the direct effectiveness of Helicobacter pylori eradication (HPE) on the remnant stomach neoplasms after curative gastrectomy. This study aims to assess whether HPE could prevent the development of gastric neoplasms in the remnant stomach after curative gastrectomy through a double-blinded, randomized controlled trial. Methods After curative gastrectomy, patients with HP infection and pathologically proven stage 1 tumors will be enrolled and randomly assigned to eradication (n = 492) and placebo (n = 492) groups. Patients in the eradication arm will be given the eradication regimen, which will comprise 40 mg of esomeprazole, 1 g of amoxicillin, and 500 mg of clarithromycin twice a day for 14 days. The primary endpoint is the development of gastric neoplasms, including adenoma or adenocarcinoma. The secondary endpoints are the 10-year overall survival, improvement rates of gastric glandular atrophy and/or intestinal metaplasia, and incidence of new-onset hyperplastic polyps among the groups. Significance This research will be the first randomized controlled clinical study in which a thorough long-term follow-up will be needed to evaluate the effectiveness of HPE for remnant stomach neoplasms after curative gastrectomy. Its results will serve as a basis for developing future strategies in the management of patients with HP infection who undergo curative gastrectomy. Trial registration https://cris.nih.go.kr/ KCT0008855. October 10, 2023.